Snow cover variability and change in mountainous regions of Bulgaria, 19312000 - Nadezhda Petkova; Ekaterina Koleva; Vesselin Alexandrov (Meteorologische Zeitschrift, 2004)
An investigation of change in snow cover (maximum depth and snow cover duration) over the 1931-2000 period was carried out at sixteen climate stations located in mountainous areas of Bulgaria. The mountain climate has been characterized by widespread warming and decreased winter precipitation over this period. However, there was no evidence of similar large-scale reductions in snow depth or snow cover duration: some sites showed significant decreases in snow cover, some no change, while others showed significant increases. Further analysis is required to understand the reasons for the varied response of snow cover to a changing climate.